Galectin Family Members: Emerging Novel Targets for Lymphoma Therapy? - Shi, Yuanwei; Tang, Danting; Li, Xiaoqi; Xie, Xiaoli; Ye, Yufu; Wang, Lijuan (Frontiers in Oncology, 2022)
The galectin family of proteins has high affinity with β-galactoside-containing glycans. These proteins participate in cell growth and differentiation, cell adhesion, cell signal transduction, cell apoptosis, and other cellular activities. In recent years, a large number of studies have described the expression and correlation of galectins in different tumors. Each member of the family plays a vital role in tumor growth, progression, angiogenesis, adhesion, and tumor immune escape. Studies on the roles of galectins in lymphoma have mainly involved galectin-1, -3, -7, and -9. The results suggest that galectins may become novel targets for precise tumor treatment. This article reviews current research progress regarding galectins in lymphoma and provides new ideas for exploring them as novel targets for treating lymphoma and other important medical issues.